Problematyka władzy międzynarodowej - Maj, Czesław (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2013)
One of the fundamental categories of general sociology concerns power. Regardless of differences in interpretation, power can be defined as the dependence between subordinator and subordinated. This relation is unidirectional. When discussing influence, this property is significant, as otherwise it could be reciprocal, or an influence could be exerted by many other entities that are not bound by the relationship of subordination. The nature of international relations is too specific to allow a simple transfer of power-related phenomena from the realm of domestic relations. One can indicate the presence of delegated power, resulting from the mutual assignment of subordination rights to international deci- sion-making bodies. The processes of international power are divided into procedures of hard power, soft power and smart power, the latter signifying the manifestation of effective power, making use of the mechanisms of the former two. It is also important to take into account the specificity of the legitimization of international power and manifestations of accountability. Also not without significance is the capacity for the implementation of international power, equipped with the relevant enforcement instruments.
Issues of international power
Keywords: władza; władza międzynarodowa; soft power; hard power; smart power